Characteristics of and outcomes for elderly patients with acute myocardial infarction: differences between females and males - Thang ND; Karlson BW; Karlsson T; Herlitz J (Clinical Interventions in Aging, 2016)
Nguyen Dang Thang,1 Björn Wilgot Karlson,1,2 Thomas Karlsson,3 Johan Herlitz1,4 1Department of Molecular and Clinical Medicine, Sahlgrenska University Hospital, Gothenburg, 2AstraZeneca R&D, Mölndal, 3Health Metrics, Institute of Medicine, Sahlgrenska Academy, University of Gothenburg, Gothenburg, 4School of Health Sciences, Research Centre PreHospen, University of Borås, The Pre-hospital Research Centre of Western Sweden, Borås, Sweden Objectives: This study analyzed age-adjusted sex differences among acute myocardial infarction (AMI) patients aged 75 years and above with regard to 7-year mortality (primary end point) and the frequency of angiograms and admission to the coronary care unit (CCU) as well as 1-year mortality (secondary end points).Methods: A retrospective cohort study comprised 1,414 AMI patients (748 females and 666 males) aged at least 75 years, who were admitted to Sahlgrenska University Hospital in Gothenburg, Sweden, during two periods (2001/2002 and 2007). All comparisons between female and male patients were age adjusted.Results: Females were older and their previous history included fewer AMIs, coronary artery bypass grafting procedures, and renal diseases, but more frequent incidence of hypertension. On the contrary, males had higher age-adjusted 7-year mortality in relation to females (hazard ratio [HR] 1.16 with corresponding 95% confidence interval [95% CI 1.03, 1.31], P=0.02). Admission to the CCU was more frequent among males than females (odds ratio [OR] 1.38 [95% CI 1.11, 1.72], P=0.004). There was a nonsignificant trend toward more coronary angiographies performed among males (OR 1.34 [95% CI 1.00, 1.79], P=0.05), as well as a nonsignificant trend toward higher 1-year mortality (HR 1.18 [95% CI 0.99, 1.39], P=0.06).Conclusion: In an AMI population aged 75 years and above, males had higher age-adjusted 7-year mortality and higher rate of admission to the CCU than females. One-year mortality did not differ significantly between the sexes, nor did the frequency of performed coronary angiograms. Keywords: acute myocardial infarction, elderly patients, characteristics, cardiovascular outcomes, death